Study of the Effect of Capoten and Tenormin Drugs on Lipid Profile and Renal Function in Patients with Hypertension - Esam, Mayasa; Esmaeel, Ammal (Al-Nahrain Journal of Science, 2018)
High blood pressure, also called hypertension: it is an elevated pressure of the blood in the arteries. Although the body can tolerate increased blood pressure for months and even years, eventually the heart may enlarge, which is a major factor in heart failure. Such pressure can also injure blood vessels in the heart, kidneys, the brain, and the eyes. Tenormin used to treat hypertension may be chemically described as a benzene acetamide, 4 - [21 – hydroxyl 1-3-[methyl ethyl) amino] prosody]. Tenormin has a molecular weight of 266.34 D. Capoten used to treat hypertension, chemically described as a 1-(3-mercapto-2-D-methyl-1-oxoproppyl) -l-proline (S, S), is used therapeutically as an antihypertensive agent. It acts as a potent and specific inhibitor of angiotensinogen-converting enzyme. This study includes forty patients with high blood pressure whom divided into two groups: group (A) which included twenty patients use Tenormin and group (B) which included twenty patients use Capoten, and Twenty healthy subjects group (C) with matched age, sex and BMI, were included in this study as control group. Lipid profile, urea, creatinine, albumin, glucose were determined by enzymatic method. The results of group (A) show that there were significant elevation (P< 0.05) of total cholesterol, Triglycerides, VLDL, glucose, urea and creatinine, the result also revealed negative correlation between the treatment with Tenormin with LDL and glucose. The results of group (B) revealed significant elevation (P< 0.05) of cholesterol, LDL, triglyceride, glucose, urea, creatinine and albumin. Negative correlation was found between Capoten with LDL and albumin as Conclusion Tenormin is more appropriate to treat patients with diabetes mellitus or kidney disease in addition to hypertension.